Resilience and Diversity in Financial Economics: A Paradigm Shift towards Ecological Finance Theory - Nayve Jr., Ruben M; Sistoso, Ramon; Timbang, Ferdinand (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2024)
This research investigates the paradigm shift towards Ecological Finance Theory (EFT) and its implications for resilience and diversity within financial economics. Drawing on insights from ecology, sustainability science, and complexity theory, EFT proposes a holistic approach to understanding and managing financial systems in the context of global environmental challenges and socio-economic uncertainties. The study develops a conceptual framework for EFT, emphasizing resilience and diversity as central tenets in enhancing the sustainability and stability of financial ecosystems. Central to EFT is the recognition of the interconnectedness between financial systems and the natural environment. Resilience, defined as the ability to withstand and adapt to disturbances while maintaining essential functions and structures, emerges as a key principle in navigating uncertainties and mitigating systemic risks within financial markets. Moreover, diversity, encompassing a variety of market participants, financial instruments, investment strategies, and perspectives, is crucial for fostering innovation, inclusivity, and resilience within financial ecosystems. The research findings underscore the transformative potential of EFT in reshaping financial systems towards greater sustainability and resilience. By integrating ecological principles and sustainability criteria into financial decision-making processes, EFT offers a pathway towards building a more stable, inclusive, and sustainable financial future. As financial practitioners, policymakers, and researchers increasingly embrace this holistic approach, the vision of a resilient and sustainable financial system capable of navigating the complexities of the 21st century becomes increasingly attainable.